PENERAPAN KONSEP LEADHERSHIP DAN POWERSHIP YANG IDEAL PADA TENAGA KEPENDIDIKAN - Muh Ibnu Sholeh (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
The concept of leadership is always used in various sectors, one of which is education. In the world of education, the concept of leadership is indispensable for educators. This is because educators are professionals in planning and implementing the learning process. For this reason, they are required to develop their performance or abilities through leadership. Meanwhile, the leader in the school institution is the principal. This leader plays a role in improving the performance of educators with an ideal leadership system. This analysis was conducted to see the ideal application of the concept of leadership and powership to the subject of teaching staff. The analytical method used is descriptive qualitative. From this analysis it is concluded that: the application of the concept or style of leadership for these educators has an influence on discipline, performance or ability, and responsibility. In improving discipline, school leaders apply telling and situational methods. So, educators can understand that school rules must be obeyed and implemented. Next is to improve the ability or performance of educators. The leader applies a participatory style. Leaders must build two-way communication with educators. Have full trust and respect for their performance. Finally, increase the sense of responsibility to apply a democratic style. Leaders regard educators as work partners and not subordinates. Then, the leader provides appropriate guidance and provides clear coordination of the tasks performed.